Does humanization or machinization make the IoT persuasive? The effects of source orientation and social presence - Kang, Hyunjin (2022)
The advent of Internet of Things (IoT) technology has revolutionized both the roles and functions of everyday objects and how users interact with them. Using artificial intelligence (AI) and an advanced capacity for communication, smart objects can now function as communication sources and deliver persuasive messages. This study investigates how different types of agency and source cues shape the persuasiveness of a smart object via social presence. When users interacted with a smart object that exerted its own agency, they sensed greater social presence when the object used machine cues rather than human cues. Conversely, when users interacted with a smart object that allowed the user to exercise their own agency, human cues, rather than machine cues, produced greater feelings of social presence, which enhanced the persuasiveness of the messages conveyed by the object. However, the persuasive effects of social presence were reversed when the interaction prompted AI anxiety in the user.